Severe Treatment-Resistant Methemoglobinemia of Unknown Etiology With Recurrence - James Ainsworth; Suresh Pillai (Case Reports in Critical Care, 2025)
Discussion: We report a case of a 25-year-old female with repeated admissions with methemoglobinemia. This case highlights the potential for refractory methemoglobinemia requiring repeated treatment, and the importance of longer periods of close observation. It is important to consider the diagnosis in patients without a clear trigger for methemoglobinemia, as an identifiable cause may not always be clear.